2022
DOI: 10.1038/s41598-021-04397-z
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect of Alpha-lipoic acid supplementation as a potential adjunct treatment in episodic migraines

Abstract: The current study was performed to evaluate the effects of alpha-lipoic acid (ALA) supplementation on lactate, nitric oxide (NO), vascular cell adhesion molecule-1 (VCAM-1) levels, and clinical symptoms in women with episodic migraines. Considering the inclusion and exclusion criteria, ninety-two women with episodic migraines participated in this randomized, double-blind, placebo-controlled, parallel-design trial. The participants were randomly assigned to receive either 300 mg/day ALA or placebo, twice per da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
0
8
0
4
Order By: Relevance
“…Moreover, the current study indicated that selenium supplementation has a favorable effect on patients’ quality of life. A number of previous studies have investigated the effect of various antioxidants on migraine symptoms, of which, the results of a study by Kelishadi et al showed that alpha-lipoic acid supplementation for 12 weeks had a reducing effect on the frequency and severity of headaches in women with episodic migraine ( 34 ). Another RCT revealed that curcumin and Q10 co-supplementation for 8 weeks improved the frequency, duration, and severity of headaches as well as quality of life in patients with episodic migraine ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the current study indicated that selenium supplementation has a favorable effect on patients’ quality of life. A number of previous studies have investigated the effect of various antioxidants on migraine symptoms, of which, the results of a study by Kelishadi et al showed that alpha-lipoic acid supplementation for 12 weeks had a reducing effect on the frequency and severity of headaches in women with episodic migraine ( 34 ). Another RCT revealed that curcumin and Q10 co-supplementation for 8 weeks improved the frequency, duration, and severity of headaches as well as quality of life in patients with episodic migraine ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, unlike the frequency and severity of headaches, selenium had no effect on headache duration. Previous studies have shown that headache duration has a late response to interventions designed for patients with migraine ( 16 , 34 ). Therefore, a longer duration of selenium treatment and intervention with higher doses may affect the duration of headaches in migraineurs.…”
Section: Discussionmentioning
confidence: 99%
“…The median migraine disease burden (MDB) was based on the Migraine Headache Index Score (MHIS). The MHIS has been described in detail elsewhere [22,23] and is calculated by multiplying the migraine frequency within the last 3 months (days per month) by the pain intensity (scaled from 0 to 10) and migraine attack duration (fraction of 24 h). The MDB was calculated by multiplying the median MHIS by the 3-month prevalence of migraine.…”
Section: Migraine Disease Burdenmentioning
confidence: 99%
“…A plasma concentration of as low as 0.13 μg/L of ALA is shown to correlate with migraine; thus, it is speculated as a potential biomarker in migraine (Gross et al, 2021). Recent findings have suggested that supplementation of ALA 600 mg/day as adjunct treatment in patients with migraine has imparted improvement in mitochondrial and endothelial functions, thereby alleviating the clinical symptoms (Kelishadi et al, 2022). Similarly, thiols, the sulphur containing organic compounds, readily react with ROS to form disulfides, which decreases oxidative stress (Banne et al, 2003).…”
Section: Biochemical Perspectivementioning
confidence: 99%